2021
DOI: 10.1177/00037028211055477
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectroscopy-Determined Bone Compositional Changes Associated with Anti-Resorptive Treatment of the oim/oim Mouse Model of Osteogenesis Imperfecta

Abstract: Applications of vibrational spectroscopy to assess bone disease and therapeutic interventions are continually advancing, with tissue mineral and protein composition frequently investigated. Here, we used two spectroscopic approaches for determining bone composition in a mouse model of the brittle bone disease osteogenesis imperfecta (OIM) with and without antiresorptive agent treatment (alendronate (ALN) and RANK-Fc). Near infrared (NIR) spectral analysis via a fiber optic probe and Fourier transform infrared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Drug therapy is relatively more practical and convenient in clinical practice. Multiple anti-resorptive and anabolic agents have improved the phenotype of OI bones ( Datta, Vila & Tuck, 2021 ; Shanas et al, 2022 ). However, the length of these medications’ half-life frequently results in undesirable side effects or inconveniences.…”
Section: Discussionmentioning
confidence: 99%
“…Drug therapy is relatively more practical and convenient in clinical practice. Multiple anti-resorptive and anabolic agents have improved the phenotype of OI bones ( Datta, Vila & Tuck, 2021 ; Shanas et al, 2022 ). However, the length of these medications’ half-life frequently results in undesirable side effects or inconveniences.…”
Section: Discussionmentioning
confidence: 99%
“…Attenuated total reflection (ATR) and O-PTIR spectroscopies were used to investigate several tissue compositional properties of the bone powder and intact femoral neck samples, as detailed below, and previously described. 33,35,43,44 Attenuated Total Reflection. Demineralized bone and intact tissue sections were lyophilized and analyzed using a Nicolet iS5 FT-IR spectrometer coupled to an iD7 ATR accessory with a ∼2 mm diameter diamond crystal (Thermo Scientific).…”
Section: Spectroscopic Data Collection and Analysismentioning
confidence: 99%
“…Attenuated total reflection (ATR) and O-PTIR spectroscopies were used to investigate several tissue compositional properties of the bone powder and intact femoral neck samples, as detailed below, and previously described. 33,35,43,44…”
Section: Spectroscopic Data Collection and Analysismentioning
confidence: 99%
“…In pre-clinical testing, NIR spectral analysis in the oim/oim (OIM) mouse model of moderate-to-severe OI demonstrated that cortical bone had a 50% higher overall water content in OIM compared to wildtype controls ( Fig. 10 A) ( Shanas et al, 2021 ). The authors postulate this was a result of more matrix space in OIM bone for water to ‘loosely associate with’.…”
Section: Bone Water With Age and Diseasementioning
confidence: 99%
“…C) Mineral and matrix-bound water relative to total protein was negatively correlated to stiffness (r = −0.44, p < 0.05) and D) maximum load (r = −0.60, p < 0.05). Figures from Shanas et al adapted with permission ( Shanas et al, 2021 ). …”
Section: Bone Water With Age and Diseasementioning
confidence: 99%